Solving Integral Equation Via Fixed Point Theorems in Generalized N-Fuzzy Metric Spaces - Degefa, Solomon Zerfu; Singh, Vizender; Aemro, Yohannes Gebru (Discontinuity, Nonlinearity, and Complexity, 2026)
In the present paper, we announced a new notion of ``generalized N-fuzzy metric spaces" which explores a more broad view of fuzzy metric spaces mentioned in the reviewed literatures. A fixed point theorem in the setting of Generalized N-fuzzy metric space via fuzzy n-Banach Contraction mapping was proved. Finally, we demonstrated an application of main results in solving integral equation.